Analisis Penundaan Kodifikasi terhadap Perkembangan Hukum Keluarga Islam Era Orde Lama - Muhammad Zikri; Faisar Ananda; Ibnu Radwan Siddik Turnip (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research discusses the development and implementation of Islamic family law in Indonesia during the Old Order period (1945-1966), with the aim of analyzing the dynamics of its application in the national legal system and identifying the factors that influenced it. The urgency of this research lies in the importance of understanding the historical foundation of Islamic family law as part of the formation of a pluralistic national legal system. Using a historical and normative qualitative approach, this research utilizes literature study and descriptive analysis of historical documents, legal regulations, and academic literature. The results show that Islamic family law during the Old Order period had not been formally accommodated in national legislation, but continued to live and run through religious courts and community social practices. In conclusion, although not officially codified, Islamic family law still plays an important role in the lives of Muslims and becomes an important basis for legal reform in the next era. The implication of this finding is the importance of strengthening the role of Islamic law in the national legal system through codification that is grounded in the social, cultural and religious values of Indonesian society.